2022
DOI: 10.3390/ijerph191911892
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Shade Matching Ability among Dental Students under Different Lighting Conditions: A Cross-Sectional Study

Abstract: Successful esthetic dentistry to meet patient satisfaction and produce a progressive impact on someone’s personality cannot be succeeded without proper shade selection, both for direct or indirect restoration of dentition. The accurate shade selection is one of the most interesting phases of restoring the natural look of teeth. In clinical practices, dental students should be aware of the various light sources used for shade selection. The purpose of this research is to compare the shade matching ability of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The Kappa value was found with strong correlation for observers 1, 3, 4, and 5; whereas the agreement was slight for observer 2. These results are in agreement with the studies performed by Curd, 44 Gokce, 11 Jouhar, 45 Berger, 5 and Carsten. 16 The authors concluded that the shade selection performed under the shade correcting devices used in their respective studies was significantly better than the shades selected under sunlight.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Kappa value was found with strong correlation for observers 1, 3, 4, and 5; whereas the agreement was slight for observer 2. These results are in agreement with the studies performed by Curd, 44 Gokce, 11 Jouhar, 45 Berger, 5 and Carsten. 16 The authors concluded that the shade selection performed under the shade correcting devices used in their respective studies was significantly better than the shades selected under sunlight.…”
Section: Discussionsupporting
confidence: 93%
“…Effect of the incident light has been studied in the past but these experiments have been carried out comparing the shade tabs of shade guides. 3,11,26,27,30,32,34,35,44,45 The observers in these studies were asked to select a shade of a blinded shade tab with the shade guide. The detriment of this study design is that the shade tabs are inconsistent in their coverage of tooth shades in the population as mentioned by Ahn 46 and Paravina.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of a number of researchers, clinical experience has no appreciable impact on the precision of color-matching [13,14]. Several investigations, however, indicate the opposite [15,16,17]. The study by Juliana A. Medeiros et al involved one hundred individuals, including dentists, dentistry students, dental auxiliaries, dental technicians, and laypeople, and reached the conclusion, based on their findings, that the discernment of the observer has an impact on the precision of tooth color determination.…”
Section: Discussionmentioning
confidence: 99%
“…The main tools required to produce a color-matching result are computerized spectrophotometers and colorimeters, which measure color quantitatively. Due to their extreme accuracy, spectrophotometers cannot be used in clinical settings, which occasionally impairs the thinking of the technician and clinician [ 3 ].…”
Section: Introductionmentioning
confidence: 99%